New grounded immittance simulators employing a single CFCC. Issue 8 (21st August 2017) - Singh, Alok Kumar; Kumar, Pragati; Senani, Raj
Abstract : In this study, a number of new immittance simulators employing a single current follower current conveyor (CFCC) and three passive components are proposed. First, six new circuit configurations have been introduced which can simulate lossy immittances of different types using a single CFCC along with a canonical number of passive and active components. Subsequently, with a little modification in the hardware of the CFCC, three other new circuits have been introduced which can simulate a variety of lossless immittances without any component matching constraints or requirement of additional active elements. When the passive resistors are replaced with complementary metal–oxide–semiconductor (CMOS) voltage controlled resistors, electronic tunability of the simulated immittances is available in all the cases. Several application examples of some of the proposed simulated immittance circuits have been presented and their workability has been verified using PSPICE simulations based on CFCC implementable in 0.18 μm CMOS technology.